THE ANALYSIS OF CUSTOMER INTEGRATION OF CHILDREN’S PLAY FACILITIES AT KENTUCKY FRIED CHICKEN MANADO - Yessica Dian Oktriyani Kalesaran; Paulus Kindangen; Frederik Worang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Child's attitude can influence parents purchasing decisions. Playground can affect the activities of children and parents. Companies need to consider providing and developing Playground which can also be profitable for the company. Because in Manado there is minimal availability of Playground at the Restaurant. This research doing by In Depth Interview Method. There are several things that affect customer integration with the Playground, Kids Fun, Child's Appetite, Child Safety, and Parents' Comfort. Customers will integrate well for the company if the company also pays attention to the integration that customers show. What are their desires and complaints. Customers can fulfill what they expect.